Non-anthropocentric Composition: Decentralising the Human through Contemporary Performance Practices - Reyes, Alicia; Assis, Paulo de; Willson, Rachel Beckles (Ghent Orpheus Instituut, 2028)
This doctoral proposal embarks on an artistic research project aimed at the development and refinement of my transdisciplinary compositional practice, with a distinct focus on exploring non-anthropocentric approaches to the creation of musical and multimedia works.The overarching objective is to transcend conventional paradigms that centre human beings as the main characters in musical performances, exploring alternative conceptualisations of artistic expression that prioritise interconnectedness with the broader ecological fabric.Grounded in ecological theories, biological imagination, and posthuman philosophies, this research seeks to develop new modes of art-making that engage with and reflect upon the agency of non-human entities and natural processes.This research endeavour will contribute to the emergence of new compositional languages that challenge anthropocentric norms, offering a fresh perspective on the role of the composer/director in artistic collective processes and on the transformative potential of non-anthropocentric musical practices.
2028-09-30
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music; Non-anthropocentric composition: Decentralising the human through contemporary performance practices; Ecology